ALLELOPATHIC EFFECT OF LEGUMINOUS WEEDS ON RATE, SYNCHRONIZATION AND TIME OF GERMINATION, AND BIOMASS PARTITIONING IN RICE - ZOHAIB,A. (2017)
ABSTRACT The present study was aimed at determining the allelopathic influence of water extracts at varying concentrations (2.5% and 5% w/v) and residues with varying decomposition periods (0, 15 and 30 days) at 2% (w/w) concentration of four weeds (Trigonella polycerata, Vicia sativa, Lathyrus aphaca, Medicago polymorpha) against rate, synchronization and time of germination, and biomass partitioning of rice through plant and soil bioassays. Germination and biomass partitioning in rice plants were inhibited by extracts and residues. The maximum decrease in energy of germination (88.6%) and increase in time for 50% germination (210.4%) were caused by the L. aphaca extract at 5% concentration as compared to control. Root and shoot, fresh weight (13.6 and 28.6%, respectively) and dry weight (20.4 and 41.7%, respectively) were reduced by the M. polymorpha extract at 5% concentration. The Vicia sativa extract at both concentrations caused a great increase in the root/shoot ratio (125-145.8%). Trigonella polycerata and V. sativa residues decomposed for 30 days caused maximum inhibition of energy of emergence (71.4%) and their decomposition for zero and 15 days, respectively, inhibited coefficient of uniformity of emergence (78.9%). Medicago polymorpha and L. aphaca residues decomposed for 30 days exaggerated time for 50% emergence (47.1 and 50.3%, respectively) when compared with control. Medicago polymorpha residues decomposed for 30 days exerted the greatest inhibitory effect on shoot fresh weight (46.1%) and root dry weight (59.9%). Vicia sativa with 30 days and T. polycerata residues without decomposition produced the least root fresh weight (65.3%) and shoot dry weight (52.6%), respectively. The root/shoot ratio (56.8%) was increased by T. polycerata residues without decomposition. Phenolics from leguminous weeds caused inhibition of germination/emergence and biomass partitioning in rice. Therefore, these weeds must be eradicated from the field at their initial growth stages.